Productivity and Production Prediction of Paddy in Bengkulu Province - Azhari, Diah (SINTA Journal (Science, Technology, and Agricultural), 2024)
Paddy production and productivity are crucial indicators in determining the success of a region's agricultural sector. Bengkulu Province has potential in the agricultural sector, particularly in paddy production. The data obtained show that paddy production and land area have been quite fluctuating. The aim of this research is to identify productivity and forecast future agricultural production. By using predictive modeling methods, this research also aims to project future paddy production. Utilizing quantitative descriptive methods and secondary data, specifically time series data of production and land area from 2004 to 2023, the data analysis employs linear regression forecasting. The results indicate that the average paddy productivity in Bengkulu Province reaches 3.4355 tons per hectare. The predicted paddy production for the next five years, from 2024 to 2028, shows a trend that tends to be stable but remains in a lower range compared to previous years. In 2024, production is predicted to reach 307,422 tons, then slightly decrease to 303,658 tons in 2025, and continue to decrease to 299,848 tons in 2026. The years 2027 and 2028 are predicted to reach 297,258 tons and 293,164 tons, respectively. This decline indicates ongoing challenges in the paddy farming sector in Bengkulu Province.